Low-light-transmittance UV adhesive and preparation method thereof

A UV adhesive formulation with epoxy resin and modified nanofillers enhances curing speed, mechanical properties, and light shielding, addressing limitations in existing low-transmittance UV adhesives for improved flexibility and low-temperature performance.

CN119242235APending Publication Date: 2025-01-03江苏矽时代材料科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411435501.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing low-transmittance UV adhesives face limitations in curing rate, mechanical properties, and applicability in low-temperature dry environments, particularly in photocurable cationic systems, and lack effective light shielding and flexibility.

Method used

A low-transmittance UV adhesive formulation comprising epoxy resin, rubber-modified epoxy resin, epoxy monomer, modified nanofiller, and specific additives, which promotes rapid curing and enhances mechanical properties, heat resistance, and light scattering for improved light shielding.

Benefits of technology

The adhesive achieves rapid curing, high shear strength, excellent heat resistance, and reduced light transmittance, with improved flexibility and impact resistance, suitable for low-temperature applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005084829270000011
    Figure BDA0005084829270000011
  • Figure BDA0005084829270000021
    Figure BDA0005084829270000021
  • Figure BDA0005084829270000071
    Figure BDA0005084829270000071
Patent Text Reader

Abstract

The invention discloses a low-light-transmittance UV adhesive and a preparation method thereof. The low-light-transmittance UV adhesive comprises the following raw materials in parts by weight: 100 parts of epoxy resin; 20 to 25 parts of rubber modified epoxy resin; 50 to 60 parts of an epoxy monomer; 8 to 10 parts of a silane coupling agent; 25 to 30 parts of a modified nano filler; 55 to 65 parts of an amine accelerator; 3-7 parts of a photoinitiator; 1-2 parts of a stabilizer; 3-8 parts of fumed silica; 2-4 parts of a defoaming agent; 2-3 parts of an assistant accelerant; 2-4 parts of a matting agent; 8 to 15 parts of oxbutyl ring; and 0.05 to 0.1 part of a black pigment. The epoxy resin, the rubber modified epoxy resin, the epoxy monomer, the modified nano filler and other raw material components are matched for use, so that the heat resistance and corrosion resistance of the adhesive can be improved while the mechanical properties (such as hardness, shear strength and the like) of the adhesive are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesives and relates to a UV adhesive, in particular to a low-light-transmittance UV adhesive and a preparation method thereof. Background Art

[0002] The curing method of UV adhesives is usually to add photoinitiators to polymerize the free radicals or cations in the system for curing. Sufficient light energy penetration has a great influence on the curing integrity of the system, so the transmittance of the UV adhesive system has higher requirements.

[0003] In UV adhesive systems with low light transmittance, photosensitizers or photosensitizers are generally used to promote curing, but the addition of such additives has little effect on light penetration. In photocurable free radical low-transmittance systems, sulfides such as polythiols are generally used as promoters to achieve the expected curing effect, but in photocurable cationic systems, the addition of promoters such as polythiols does not significantly affect the curing rate of the system; therefore, the use of low-transmittance UV adhesives is limited. At present, low-transmittance adhesives are generally cured by heat curing or moisture curing, and their application in general low-temperature dry environments is relatively limited, so the demand for low-transmittance UV adhesives is more urgent.

[0004] The Chinese invention patent with application number 201910264777.1 discloses a UV-curable adhesive and its preparation method. The adhesive includes the following components by weight: 40-55 parts of photocurable resin, 40-50 parts of acrylate active monomer, 3-10 parts of photoinitiator, and 0.5-8 parts of carbon black; during the preparation of the adhesive, a mercury lamp or UV LED lamp with a wavelength of 250-760nm is used for irradiation and curing. The low-transmittance UV-curable adhesive prepared in this way has a transmittance of <0.1% at a wavelength of 270-800nm. It is suitable for rapid packaging of anti-leakage components such as full display screen frames, camera lenses, and mobile phones. It has the advantages of rapid curing, high light shielding, and low water absorption, but physical properties such as flexibility and impact resistance need to be improved. Summary of the invention

[0005] In order to solve the above technical problems, the purpose of the present invention is to provide a low-transmittance UV adhesive which has a short curing time and a long room temperature stability time under low light transmittance conditions after short-term low-energy UV light irradiation; and has excellent mechanical properties, heat resistance and corrosion resistance.

[0006] In order to achieve the above object, the present invention provides a low-transmittance UV adhesive, the raw materials of which include the following components in parts by weight:

[0007]

[0008]

[0009] Optimally, the epoxy resin is a bisphenol A epoxy resin, the rubber-modified epoxy resin is a liquid bisphenol A epoxy resin modified with polybutadiene, and the epoxy monomer is a mixture of one or two selected from 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate and bis((3,4-epoxycyclohexyl)methyl)adipate.

[0010] Optimally, the silane coupling agent is a mixture of one or more selected from γ-glycidyloxypropyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane and γ-aminopropyltriethoxysilane.

[0011] Optimally, the modified nanofiller is a mixture of one or more selected from modified aluminum oxide, modified zinc oxide, modified calcium carbonate and modified magnesium oxide.

[0012] Furthermore, the modified nano filler is modified nano calcium carbonate, which is made by surface treatment with an aluminate coupling agent of at least one selected from nano calcium carbonate with a particle size of 25 to 100 nm.

[0013] Optimally, the amine accelerator is a mixture of one or more selected from aliphatic polyamines, alicyclic polyamines, aromatic polyamines and polyamides.

[0014] Furthermore, the amine accelerator is a mixture of aliphatic polyamine and alicyclic polyamine, preferably a mixture of hexamethylenediamine and isophoronediamine.

[0015] Optimally, the photoinitiator is a mixture of one or more selected from Michler's ketone, quaternary ammonium salts and oxime esters, the stabilizer is a mixture of one or more selected from p-hydroxyanisole, hydroquinone and tetrachlorobenzoquinone, the fumed silica is fumed silica with a particle size of 10 to 20 nm, the defoamer is an acrylate defoamer or a silicone defoamer, the co-accelerator is a mixture of one or more selected from saccharin, tetramethylthiourea and phthalimide, and the matting agent is a metal soap matting agent, which is a mixture of one or more selected from calcium stearate, aluminum stearate and zinc stearate.

[0016] Another object of the present invention is to provide a method for preparing the above-mentioned low-transmittance UV adhesive, comprising mixing a formula amount of epoxy resin, rubber-modified epoxy resin, epoxy monomer, oxadiazole, silane coupling agent, modified nanofiller, black pigment, photoinitiator, defoamer, fumed silica, stabilizer, co-accelerator and matting agent, cooling the mixture to 20-25° C., adding a formula amount of the amine accelerator and stirring the mixture evenly.

[0017] The low-transmittance UV adhesive of the present invention can improve the mechanical properties (such as hardness, shear strength, etc.) of the adhesive while also improving the heat resistance and corrosion resistance of the adhesive by combining raw material components such as epoxy resin, rubber-modified epoxy resin, epoxy monomer, and modified nanofiller; specifically, the following synergistic effects are produced: after receiving UV light, the curing of the adhesive can be promoted, so that it exhibits good strength in a shorter time, and the hard and brittle characteristics of the bisphenol A epoxy resin itself are improved, so that the adhesive takes into account the flexibility and impact resistance of the rubber-modified adhesive and the mechanical properties of the bisphenol A epoxy resin. In addition, the low-transmittance UV adhesive also has good thixotropic properties, increasing the light scattering on the adhesive surface to improve the light shielding property and thus reduce the light transmittance. DETAILED DESCRIPTION

[0018] The low-transmittance UV adhesive of the present invention comprises the following components in parts by weight: 100 parts of epoxy resin; 20-25 parts of rubber-modified epoxy resin; 50-60 parts of epoxy monomer; 8-10 parts of silane coupling agent; 25-30 parts of modified nano filler; 55-65 parts of amine accelerator; 3-7 parts of photoinitiator; 1-2 parts of stabilizer; 3-8 parts of gas-phase silica; 2-4 parts of defoamer; 2-3 parts of co-accelerator; 2-4 parts of matting agent; 8-15 parts of oxetane; and 0.05-0.1 parts of black pigment. By combining raw materials such as epoxy resin, rubber-modified epoxy resin, epoxy monomer, and modified nanofiller, the mechanical properties (such as hardness, shear strength, etc.) of the adhesive can be improved while also improving the heat resistance and corrosion resistance of the adhesive; specifically, the following synergistic effects are produced: after being exposed to UV light, the curing of the adhesive can be promoted, so that it exhibits good strength in a shorter period of time, and the hard and brittle characteristics of the bisphenol A epoxy resin itself can be improved, so that the adhesive can take into account the flexibility and impact resistance of the rubber-modified adhesive and the mechanical properties of the bisphenol A epoxy resin. In addition, low-transmittance UV adhesives also have good thixotropic properties, which increase the light scattering on the adhesive surface, improve the light-shielding properties, and thus reduce the transmittance.

[0019] Optimally, the epoxy resin is a bisphenol A epoxy resin, the rubber-modified epoxy resin is a liquid bisphenol A epoxy resin modified by polybutadiene, and the epoxy monomer is a mixture of one or two selected from 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate and bis((3,4-epoxycyclohexyl)methyl)adipate. Optimally, the silane coupling agent is a mixture of one or more selected from γ-glycidyloxypropyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane and γ-aminopropyltriethoxysilane. Optimally, the modified nanofiller is a mixture of one or more selected from modified alumina, modified zinc oxide, modified calcium carbonate and modified magnesium oxide; further, the modified nanofiller is a modified nano calcium carbonate, which is made by surface treatment of at least one selected from nano calcium carbonate with a particle size of 25 to 100 nm with an aluminate coupling agent. Optimally, the amine accelerator is a mixture of one or more selected from aliphatic polyamines, alicyclic polyamines, aromatic polyamines and polyamides; further, the amine accelerator is a mixture of aliphatic polyamines and alicyclic polyamines, preferably a mixture of hexamethylenediamine and isophoronediamine. Optimally, the photoinitiator is a mixture of one or more selected from Michler's ketone, quaternary ammonium salts and oxime esters, the stabilizer is a mixture of one or more selected from p-hydroxyanisole, hydroquinone and tetrachlorobenzoquinone, the fumed silica is a fumed silica with a particle size of 10 to 20 nm, the defoamer is an acrylate defoamer or an organosilicon defoamer, the co-accelerator is a mixture of one or more selected from saccharin, tetramethylthiourea and phthalimide, and the matting agent is a metal soap matting agent, which is a mixture of one or more selected from calcium stearate, aluminum stearate and zinc stearate.

[0020] The preparation method of the low-transmittance UV adhesive is as follows: after mixing the formulated amount of epoxy resin, rubber-modified epoxy resin, epoxy monomer, oxadiazole, silane coupling agent, modified nanofiller, black pigment, photoinitiator, defoamer, fumed silica, stabilizer, co-accelerator and matting agent, the mixture is cooled to 20-25° C.; and the formulated amount of the amine accelerator is added and stirred evenly.

[0021] In order to enable those skilled in the art to better understand the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only embodiments of a part of the present invention, rather than all embodiments. Based on the embodiments of the present invention, all other embodiments obtained under the premise of equivalent changes and modifications made by ordinary technicians in the field should belong to the scope of protection of the present invention.

[0022] Example 1

[0023] This embodiment provides a low-transmittance UV adhesive, comprising the following raw materials:

[0024] 100g of bisphenol A epoxy resin, 20g of liquid bisphenol A epoxy resin modified by polybutadiene, 50g of epoxy monomer, 10g of oxadiene, 8g of silane coupling agent, 25g of modified nanofiller (modified nano calcium carbonate), 0.05g of black pigment, 60g of amine accelerator, 5g of photoinitiator, 3g of defoaming agent, 5g of fumed silica, 1g of stabilizer, 2g of co-accelerator and 2g of matting agent.

[0025] The bisphenol A epoxy resin is commercially available 828, the polybutadiene-modified liquid bisphenol A epoxy resin is MX154 from Kaneka Chemical Co., Ltd., the epoxy monomer is commercially available 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate, the oxetane is commercially available oxetane, and the silane coupling agent is γ-glycidyloxypropyltrimethoxysilane; the black pigment is Mitsubishi Chemical MA100, the amine accelerator is a mixture of hexamethylenediamine and isophoronediamine in a molar ratio of 1:9, the photoinitiator is Anage Chemical's Michler's ketone, the defoamer is an acrylate defoamer (using Shenzhu Chemical's 5055), the fumed silica is a commercially available fumed silica with a particle size of 15 nm, the stabilizer is commercially available p-hydroxyanisole, the co-accelerator is commercially available saccharin, and the matting agent is commercially available calcium stearate.

[0026] The preparation method of modified nano calcium carbonate is as follows: commercially available 50nm (average particle size) nano calcium carbonate (1kg is used in this example for backup) and aluminate coupling agent (DL-411, the amount is 5% of the mass of nano calcium carbonate) are mixed at high speed (stirred at 3000r / min for 30min) for surface treatment.

[0027] The preparation method of the low-transmittance UV adhesive is as follows:

[0028] In a yellow light room, bisphenol A epoxy resin, liquid bisphenol A epoxy resin modified by polybutadiene, epoxy monomer, oxadiene, silane coupling agent, modified nanofiller, black pigment, photoinitiator, defoamer, fumed silica, stabilizer, accelerator and matting agent are added to a high-speed dispersing kettle according to the above amounts, stirred at a speed of 1500 r / min for 2 hours, and cooled using a water cooling system of the high-speed dispersing kettle;

[0029] After the temperature drops to room temperature, move the material to a planetary stirring kettle, add an amine accelerator, stir for 10 minutes at a speed of 15 Hz, a constant temperature of 20°C, and a vacuum degree of -0.09 MPa (measured by an instrument produced by China Leierda Instrument Co., Ltd., No. YL10207224), and then discharge the material and store it at -10 to 20°C.

[0030] The curing method of the low transmittance UV adhesive is to use a mercury lamp or LED lamp with a wavelength of 300 to 760 nm or a mixture of several wavelengths. Preferably, the wavelength of the light is a mixture of one or several wavelengths of 300 to 405 nm, and the curing energy is 600 to 1000 mj / cm 2 Radiation curing is performed.

[0031] Example 2

[0032] This embodiment provides a low-transmittance UV adhesive and a preparation method thereof, which is basically the same as that in Embodiment 1, except that: 100 g of bisphenol A epoxy resin, 20 g of liquid bisphenol A epoxy resin modified by polybutadiene, 50 g of epoxy monomer, 10 g of oxadiene, 8 g of silane coupling agent, 25 g of modified nanofiller, 0.06 g of black pigment, 60 g of amine accelerator, 5 g of photoinitiator, 3 g of defoamer, 5 g of fumed silica, 1 g of stabilizer, 2.5 g of co-accelerator and 2 g of matting agent;

[0033] The modified nano calcium carbonate is a nano calcium carbonate with a particle size of 100 nm that has been surface treated with an aluminate coupling agent, a photoinitiator is a quaternary ammonium salt photobase generator (commercially available compound 224), a stabilizer is 1,4-naphthoquinone, and a co-accelerator is tetramethylthiourea.

[0034] Example 3

[0035] This embodiment provides a low-transmittance UV adhesive and a preparation method thereof, which is basically the same as that in Embodiment 1, except that: 100 g of bisphenol A epoxy resin, 25 g of liquid bisphenol A epoxy resin modified by polybutadiene, 60 g of epoxy monomer, 8 g of oxadiene, 8 g of silane coupling agent, 30 g of modified nanofiller, 0.06 g of black pigment, 65 g of amine accelerator, 6 g of photoinitiator, 3 g of defoamer, 5 g of fumed silica, 1 g of stabilizer, 3 g of co-accelerator and 2 g of matting agent;

[0036] The brand of bisphenol A epoxy resin is 828, the epoxy monomer is bis((3,4-epoxycyclohexyl)methyl)adipate, the silane coupling agent is γ-(methacryloyloxy)propyltrimethoxysilane, the modified nanofiller is modified nano calcium carbonate with a particle size of 25 nm after surface treatment with aluminate; the black pigment is MA100, the amine accelerator is a mixture of hexamethylenediamine and isophoronediamine in a molar ratio of 1:5, the photoinitiator is an oxime ester photobase generator (commercially available compound 216), the defoamer is a silicone defoamer (Kashida Chemical 163), the fumed silica is fumed silica with a particle size of 18 nm, the stabilizer is tetrachlorobenzoquinone, the co-accelerator is tetramethylthiourea, and the matting agent is aluminum stearate.

[0037] Example 4

[0038] The present embodiment provides a low-transmittance UV adhesive and a preparation method thereof, which is basically the same as that in Example 1, except that: 100 g of bisphenol A epoxy resin, 20 g of liquid bisphenol A epoxy resin modified by polybutadiene, 60 g of epoxy monomer, 10 g of oxadiene, 10 g of silane coupling agent, 30 g of modified nanofiller, 0.08 g of black pigment, 65 g of amine accelerator, 6 g of photoinitiator, 4 g of defoamer, 6 g of fumed silica, 1.5 g of stabilizer, 3 g of co-accelerator and 3 g of matting agent.

[0039] Example 5

[0040] This embodiment provides a low-transmittance UV adhesive and a preparation method thereof, which is basically the same as that in Example 1, except that: 100 g of bisphenol A epoxy resin, 25 g of polybutadiene-modified liquid bisphenol A epoxy resin, 60 g of epoxy monomer, 8 g of oxetane, 9 g of silane coupling agent, 30 g of modified nanofiller, 0.1 g of black pigment, 65 g of amine accelerator, 6 g of photoinitiator, 2 g of defoamer, 8 g of fumed silica, 2 g of stabilizer, 3 g of co-accelerator and 3 g of matting agent, and the photoinitiator is a quaternary ammonium salt photobase generator (Compound 224).

[0041] Example 6

[0042] The present embodiment provides a low-transmittance UV adhesive and a preparation method thereof, which is basically the same as that in Example 1, except that: 100 g of bisphenol A epoxy resin, 22 g of polybutadiene-modified liquid bisphenol A epoxy resin, 55 g of epoxy monomer, 12 g of oxadiene, 9 g of silane coupling agent, 28 g of modified nanofiller, 0.06 g of black pigment, 60 g of amine accelerator, 5 g of photoinitiator, 3 g of defoamer, 5 g of fumed silica, 1.5 g of stabilizer, 2.5 g of co-accelerator and 3 parts of matting agent.

[0043] Comparative Example 1

[0044] This example provides a UV adhesive and a preparation method thereof, which is basically the same as that in Example 1, except that liquid low molecular weight (US Huntsman N280) nitrile rubber is used instead of polybutadiene-modified liquid bisphenol A epoxy resin.

[0045] Comparative Example 2

[0046] This example provides a UV adhesive and a preparation method thereof, which is basically the same as that in Example 1, except that an alicyclic amine accelerator (Renbang Epoxy Material 9800) is used instead of the mixture of hexamethylenediamine and isophoronediamine.

[0047] Comparative Example 3

[0048] This example provides a UV adhesive and a preparation method thereof, which is basically the same as that in Example 1, except that unmodified nano-calcium carbonate of the same particle size is used instead of modified nano-calcium carbonate.

[0049] Comparative Example 4

[0050] This example provides a UV adhesive and a preparation method thereof, which is basically the same as that in Example 1, except that no matting agent is added.

[0051] Comparative Example 5

[0052] This example provides a UV adhesive and a preparation method thereof, which is basically the same as that in Example 1, except that the photoinitiator system of the UV adhesive is replaced: triarylsulfonium salt (Nanjing Walli 1176) is used instead of quaternary ammonium salt, and polythiol (Zhuoben Chemical 6640) is used instead of amine accelerator.

[0053] The UV adhesives in Examples 1 to 6, Comparative Examples 1 to 5 and the competitive product DELO were tested for shear strength, high temperature resistance, light transmittance, curing time and stable storage time at 25°C. The test results are shown in Table 1 below.

[0054] Table 1 Performance of products in Examples 1 to 6, Comparative Examples 1 to 5 and competitor DELO

[0055]

[0056] As shown in Table 1, the low transmittance UV adhesive of the present invention has a faster curing speed in an alkaline system than in an acidic system, and has high shear strength and excellent heat resistance. Compared with the competitive product DELO, the low transmittance UV adhesive of the present invention has the characteristics of fast curing speed and stable storage at room temperature. In the case of a low transmittance UV system, increasing the amount of accelerator can shorten the curing time, but it has a greater impact on storage stability.

[0057] The above description is only a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. At the same time, the above description should be understandable and implementable for those with ordinary knowledge in the relevant technical field. Therefore, other equivalent changes or modifications that do not deviate from the concepts disclosed in the present invention should be included in the scope of protection of the present invention.

Claims

1. A low transmittance UV adhesive, characterized in that: Its raw materials include the following components in parts by weight: Epoxy resin 100 parts; Rubber modified epoxy resin 20-25 parts; Epoxy monomer 50-60 parts; Silane coupling agent 8-10 parts; 25-30 parts of modified nanofiller; 55~65 parts of amine accelerator; 3~7 parts of photoinitiator; 1~2 parts of stabilizer; 3-8 parts of fumed silica; 2~4 parts of defoaming agent; 2~3 parts of accelerator; 2~4 parts of matting agent; 8-15 parts of oxadiazine; Black pigment 0.05~0.1 parts.

2. The low-transmittance UV adhesive according to claim 1, characterized in that: The epoxy resin is a bisphenol A epoxy resin, the rubber-modified epoxy resin is a liquid bisphenol A epoxy resin modified with polybutadiene, and the epoxy monomer is one or a mixture of two selected from 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate and bis((3,4-epoxycyclohexyl)methyl)adipate.

3. The low-transmittance UV adhesive according to claim 1, characterized in that: The silane coupling agent is a mixture of one or more selected from γ-glycidyloxypropyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane and γ-aminopropyltriethoxysilane.

4. The low-transmittance UV adhesive according to claim 1, characterized in that: The modified nano filler is a mixture of one or more selected from modified aluminum oxide, modified zinc oxide, modified calcium carbonate and modified magnesium oxide.

5. The low-transmittance UV adhesive according to claim 4, characterized in that: The modified nano filler is modified nano calcium carbonate, which is made by surface treatment with an aluminate coupling agent on at least one selected from nano calcium carbonates with a particle size of 25 to 100 nm.

6. The low-transmittance UV adhesive according to claim 1, characterized in that: The amine accelerator is a mixture of one or more selected from aliphatic polyamines, alicyclic polyamines, aromatic polyamines and polyamides.

7. The low-transmittance UV adhesive according to claim 6, characterized in that: The amine accelerator is a mixture of aliphatic polyamine and alicyclic polyamine, preferably a mixture of hexamethylenediamine and isophoronediamine.

8. The low-transmittance UV adhesive according to claim 1, characterized in that: The photoinitiator is a mixture of one or more selected from Michler's ketone, quaternary ammonium salts and oxime esters, the stabilizer is a mixture of one or more selected from p-hydroxyanisole, hydroquinone and tetrachlorobenzoquinone, the fumed silica is fumed silica with a particle size of 10 to 20 nm, the defoamer is an acrylate defoamer or an organosilicon defoamer, the co-accelerator is a mixture of one or more selected from saccharin, tetramethylthiourea and phthalimide, and the matting agent is a metal soap matting agent, which is a mixture of one or more selected from calcium stearate, aluminum stearate and zinc stearate.

9. The method for preparing the low-transmittance UV adhesive according to any one of claims 1 to 8, characterized in that: The epoxy resin, rubber-modified epoxy resin, epoxy monomer, oxadiazole, silane coupling agent, modified nanofiller, black pigment, photoinitiator, defoamer, fumed silica, stabilizer, co-accelerator and matting agent are mixed and stirred, and then cooled to 20-25° C.; the amine accelerator is added and stirred evenly.